Enzymatic Glucose Biosensor Based on TbYxOy Electrolyte-Insulator-Semiconductor. Issue 8 (1st January 2016) - Weng, Wen-Hui; Wang, Chih-Wei; Pang, See-Tong; Pan, Tung-Ming
Abstract : We report herein a glucose biosensor based on glucose oxidase (GOD) immobilized on TbYx Oy sensing film grown by reactive cosputtering. The structural properties of TbYx Oy sensing films annealed at different temperatures (600, 700, 800, and 900°C) were performed using X-ray photoelectron spectroscopy and atomic force microscopy to identify the optimal annealing condition. The TbYx Oy electrolyte-insulator-semiconductor (EIS) sensor annealed at 900°C exhibited a higher sensitivity of 59.79 mV/pH, a lower hysteresis voltage of 1 mV, and a smaller drift rate of 0.26 mV/h than did those prepared at the other annealing temperatures. We attribute this behavior to the formation of a honeycomb-like structure and a decrease in the amount of lattice defects improving the stoichiometry of TbYx Oy film. Furthermore, we compared two surface modification techniques with 3-aminopropyltriethoxysilane (APTES) and APTES+glutaraldehyde (GA) to functionalize the TbYx Oy film surface and thus the enzymatic GOD was covalently immobilized on the modified surface of a TbYx Oy EIS sensor. The TbYx Oy glucose biosensor treated with APTES+GA has a high sensitivity (19.85 mV/mM) in solutions containing glucose at concentrations in the range 2–8 mM. This TbYx Oy EIS biosensor is adequate for general clinical examination of blood glucose.